2003
DOI: 10.1017/s001216220300046x
|View full text |Cite
|
Sign up to set email alerts
|

Prognosis of haemorrhagic stroke in childhood: a long-term follow-up study

Abstract: Little is known about long-term physical sequelae, cognitive functioning, and quality of life of children who have had a haemorrhagic stroke. Fifty-six patients (29 females, 27 males) under 16 years of age at time of the bleeding were studied. Mean age at time of bleeding was 7.7 years (range 1 month to 15.9 years). The primary site and cause of the bleeding at baseline were determined. Occurrences of death, re-bleedings, and seizures during follow-up were recorded. Patients who survived were invited for a fol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

14
49
1
5

Year Published

2008
2008
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 51 publications
(69 citation statements)
references
References 19 publications
14
49
1
5
Order By: Relevance
“…This is consistent with other series of SICH in childhood [14, 17, 19, 21]. In various studies dealing with cerebral AVM, hemorrhage was found to be most frequent clinical manifestation, occurring in 55–75% of patients in all age groups [18,19,20,21,22].…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This is consistent with other series of SICH in childhood [14, 17, 19, 21]. In various studies dealing with cerebral AVM, hemorrhage was found to be most frequent clinical manifestation, occurring in 55–75% of patients in all age groups [18,19,20,21,22].…”
Section: Discussionsupporting
confidence: 90%
“…Hematological abnormalities are reported to be the major risk factor in 10–30% of SICH in most series [8, 14]. Hematological causes of IPH include thrombocytopenia, hemophilia and coagulopathies.…”
Section: Discussionmentioning
confidence: 99%
“…Patients with brain tumours, bleeding diatheses, anaemia (including SCD11), leukaemia and metabolic disease are also at risk. Compared with ischaemic stroke (fig 1B–F), mortality is higher (8–40%) and recurrence is lower (in a population-based study, 13% for those with medical aetiologies, mainly acutely, and a 5-year cumulative recurrence rate of 13% for those with unoperated AVMs or tumours9), although functional outcome may be better, although only a quarter of patients have no physical or cognitive impairment 12…”
mentioning
confidence: 96%
“…The underlying cause or trigger may be a diagnostic clue to the distinction between ATS, VST and stroke mimics5 18 (figs 3–5). AIS and VST are associated with death in 6–16%12 19 and 3–8% of patients,15 20 respectively, higher in those with premorbid conditions (figs 3, 4) and in the critically ill,19 while 40–60% of both groups have significant disability 17 21. Recurrence rates are age and diagnosis dependent: 3% in neonates,13 6% (3% cerebral) after VST in children 2 years of age with no evidence for recurrence after neonatal VST,20 and 10% stroke with an additional 20–35% transient ischaemic events (TIAs) after AIS in childhood 2224…”
mentioning
confidence: 99%
“…14 Most outcome studies have focused on deficits determined by a neurologist or other health care professional. However, to understand the lasting impact of stroke on the day-to-day life of survivors, measures of health status are most informative.…”
mentioning
confidence: 99%